Non-surgical periodontal therapy with and without hyaluronic acid gel in type 2 diabetic stage-II periodontitis patients: a randomized clinical trial - Reem Al-Abbadi; Nesma Shemais; Alaa Nawwar; Karim M. Fawzy El-Sayed (BMC Oral Health)
Abstract Background The present trial evaluated clinically and radiographically the effect of topically applied hyaluronic acid (HA) gel in conjunction with professional mechanical plaque removal (PMPR) in type 2 diabetic stage-II periodontitis patients. Methodology 26 controlled (HbA1c < 7%) type 2 diabetic stage-II grade B periodontitis patients were included in the current trial and randomly assigned to test (n = 13 patients; PMPR + HA) or control (n = 13; PMPR) groups. At baseline, three- and six-months clinical attachment level (CAL; primary outcome), probing pocket depth (PPD), gingival recession depth (GRD), bleeding on probing (BOP), O’Leary plaque index (PI), HbA1c level, radiographic bone density (RBD) and defect depth (DD; all secondary outcomes) were assessed. Results Although CAL, PPD, BOP, PI, DD and RBD independently significantly improved in the PMPR + HA and the PMPR groups (p < 0.05), no significant differences were notable between both groups. HbA1c significantly decreased solely in the PMPR + HA group (p < 0.05). Conclusion Type 2 diabetic patients with stage-II periodontitis, benefit clinically from PMPR in the presence or absence of adjunctive HA gel application. Interestingly, HA as an adjunct to PMPR significantly improved HbA1c levels in controlled type 2 diabetic stage-II periodontitis patients. Trial registration The study was registered in the US National Institutes of Health Clinical Trials Registry (NCT05543434) in September 2022.